Brownian and thermophoresis diffusion effects on magnetohydrodynamic Reiner–Philippoff nanofluid flow past a shrinking sheet - Iskandar, Waini; Khairum, Hamzah; Najiyah Safwa, Khashi’ie; Nurul Amira, Zainal; Abdul Rahman, Mohd Kasim; Anuar, Ishak; Pop, Ioan (Elsevier B.V., 2023)
The aim of this paper is to highlight the output of the investigation on the MHD and radiative flow and thermal characteristics of a non-Newtonian Reiner–Philippoff nanofluid with Brownian and thermophoresis diffusion effects. The model studied is embedded in the Buongiorno theory. This unique model is designed to observe both shear thickening and shear thinning properties on that particular fluid with embedded Brownian and thermophoresis diffusion implications. The proposed model consists of continuity, momentum, energy, and concentration equations constructed using the theoretical assumptions and are reduced to a set of ordinary differential equations (ODEs) before solving it using the bvp4c function in MATLAB software. Two solutions are observed, and their physical significance is justified using the temporal stability analysis. From the standpoint of the Reiner–Philippoff fluid parameter, the skin friction coefficient as well as the heat and mass transfer rates are at maximum for the shear-thickening fluid followed by the Newtonian and shear-thinning fluids. The thermophoresis parameter is noticed to decline the heat and mass transfer rate whereas the Brownian motion parameter boosts the mass transfer rate but decreases the heat transfer rate.